2018
DOI: 10.1016/j.celrep.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The Probability of Neurotransmitter Release Governs AMPA Receptor Trafficking via Activity-Dependent Regulation of mGluR1 Surface Expression

Abstract: SummaryA major mechanism contributing to synaptic plasticity involves alterations in the number of AMPA receptors (AMPARs) expressed at synapses. Hippocampal CA1 synapses, where this process has been most extensively studied, are highly heterogeneous with respect to their probability of neurotransmitter release, P(r). It is unknown whether there is any relationship between the extent of plasticity-related AMPAR trafficking and the initial P(r) of a synapse. To address this question, we induced metabotropic glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 95 publications
(118 reference statements)
3
45
0
Order By: Relevance
“…Circles indicate a SEP-GluA2 punctum at the synapse opposed to the FM4-64 labeling. Reproduced from Sanderson et al (2018) under CC BY-NC-ND license.…”
Section: Pre-and Post-synaptic Proteins Are Aligned At the Submicron mentioning
confidence: 99%
See 2 more Smart Citations
“…Circles indicate a SEP-GluA2 punctum at the synapse opposed to the FM4-64 labeling. Reproduced from Sanderson et al (2018) under CC BY-NC-ND license.…”
Section: Pre-and Post-synaptic Proteins Are Aligned At the Submicron mentioning
confidence: 99%
“…Dye in external membranes can then be washed out, leaving only those internalized vesicles that can be visualized as puncta by confocal or multiphoton microscopy and when photo converted can be visualized in synaptic vesicles by electron microscopy (Harata et al, 2001;Branco et al, 2008). The development of agents that reduce background FM staining (Kay et al, 1999;Pyle et al, 1999) have enabled the use of this technique in brain slice preparations (Johnstone and Raymond, 2013;Sanderson et al, 2018) as well as facilitating their use in dissociated culture (Tokuoka and Goda, 2008).…”
Section: Measurement Of P(r) Using Fm Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism may involve activation of mGluR1, leading to inhibition of SK channels that ordinarily limit the synaptic activation of NMDARs (Tigaret et al, 2016). Recently, theta burst stimulation was shown to rapidly internalize mGluR1 and thereby protect high P(r) synapses from synaptic weakening (Sanderson et al, 2018). The findings reported in this study highlight an additional mechanism by which group I mGluRs might indirectly regulate LTP via modulation of the intrinsic excitability of axons.…”
mentioning
confidence: 65%
“…Therefore, ASD‐associated mutations in Shank3 may induce an alteration in the presynaptic function in hippocampal neurons that can potentially occlude the presynaptic expression of mGluR‐LTD without affecting the expression of NMDAR‐LTD. Interestingly, a recent study has shown that surface expression of mGluR1 at CA1 synapses in organotypic hippocampal slices is dependent on neuronal activity, and DHPG‐induced mGluR‐LTD occurs exclusively via the activation of mGluR1 at these synapses (Sanderson et al, ). In our current work, the expression of ASD mutations in Shank3 led to a failure of increasing the synaptic density of surface mGluR1 puncta in cultured hippocampal neurons unlike that of wild‐type Shank3 overexpressing neurons.…”
Section: Discussionmentioning
confidence: 99%